Portal Vein Embolization as an Oncosurgical Strategy Prior to Major Hepatic Resection: Anatomic, Surgical, and Technical Considerations - Orcutt, Sonia T.; Kobayashi, Katsuhiro; Sultenfuss, Mark; Hailey, Brian S.; Sparks, Anthony; Satpathy, Bighnesh; Anaya, Daniel A. (Frontiers in Surgery, 2016)
Preoperative portal vein embolization (PVE) is used to extend the indications for major hepatic resection, and it has become the standard of care for selected patients with hepatic malignancies treated at major hepatobiliary centers. To date, various techniques with different embolic materials have been used with similar results in the degree of liver hypertrophy. Regardless of the specific strategy used, both surgeons and interventional radiologists must be familiar with each other’s techniques to be able to create the optimal plan for each individual patient. Knowledge of the segmental anatomy of the liver is paramount to fully understand the liver segments that need to be embolized and resected. Understanding the portal vein anatomy and the branching variations, along with the techniques used to transect the portal vein during hepatic resection, is important because these variables can affect the PVE procedure and the eventual surgical resection. Comprehension of the advantages and disadvantages of approaches to the portal venous system and the various embolic materials used for PVE is essential to best tailor the procedures for each patient and to avoid complications. Before PVE, meticulous assessment of the portal vein branching anatomy is performed with cross-sectional imaging, and embolization strategies are developed based on the patient’s anatomy. The PVE procedure consists of several technical steps, and knowledge of these technical tips, potential complications and how to avoid the complications in each step is of great importance for safe and successful PVE, and ultimately successful hepatectomy. Because PVE is used as an adjunct to planned hepatic resection, priority must always be placed on safety, without compromising the integrity of the future liver remnant, and close collaboration between interventional radiologists and hepatobiliary surgeons is essential to achieve successful outcomes.